FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING PADA SAAT PENAWARAN UMUM SAHAM PERDANA - PRASTICA, YURENA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
This study aims to examine and analyze factors that affect the level of underpricing of shares in the company made an initial public offering (IPO). The variables studied include underwriter reputation, auditor reputation, firm size and return on asset (ROA). The study was conducted using multiple linear regression analysis. Data collection using a documentary study with purposive sampling method. From a population of 76 companies, obtained a sample of 64 companies. The result can be concluded: first, the underwriter’s reputation could not show a significant effect on the level of underpricing. Second, auditor’s reputation could not show a significant effect on the level of underpricing. Third, firm size could not show a significant effect on the level of underpricing and fourth, return on asset (ROA) successfully demonstrated a significant effect on the level of underpricing.